E-Commerce Implementation In An Effort To Consolidate The Competitiveness Of Small Industrial Businesses - Mukhlis Mukhlis; Andre Saputra; Deassy Apriani; Taufiq Taufiq (Faculty of Economics, Universitas Sriwijaya, 2023)
The technology brings changes in all aspects of life, including in business and trade. One of the technolog that are present in business and trade is e-commerce. E-commerce will provide benefits for uts users if it is used optimally, especially for small business. This study analyzes the impact of e-commerce implementation in efforts to consolidated competitiveness of small industries in ogan ilir regency. The data use is primer data used statistical analysis with comparative studies. The results of this research is MSMEs that e-commerce implementation in their business have a index higher competitiveness, greater amount of revenue and profit, as well as the total of more production or higher peoductivity from MSMEs that have not implamentation e-commerce in their business.